The Inevitable Challenge of Ethical Dilemmas in Optometry, Part 3: The Optometrist, their Patient and their Fees, a Ménage à Trois - Faucher, Caroline; Rezk, Marina; Verni, Ariana (Canadian Journal of Optometry, 2022)
Some situations place healthcare professionals in a dilemma where two ethical principles are in conflict and none of the choices are optimal. Despite the potential consequences of this quandary, no previous study has examined ethical dilemmas in optometry. Objective. This article concludes a series of three articles reporting the results of a study that sought to identify the ethical dilemmas experienced by optometrists and to describe some typical scenarios. Method. Two hundred forty optometrists completed an online survey. Results. A breach of trust can present an optometrist with a dilemma as to whether or not to maintain their relationship with the patient. The most common dilemma involves the billing of professional fees on top of the basic exam. Several other ethical dilemmas were worrisome, including those involving sexual or seductive advances by patients. Conclusion. Many ethical issues have been identified and described. These results will be useful for academic and professional bodies in helping them prepare optometrists for ethical decisions that can sometimes be difficult.